Cranberry Fruitworm Acrobasis vaccinii Riley (Lepidoptera: Pyralidae) - James T. Brown; Jennifer L. Gillett-Kaufman (EDIS)
Cranberry fruitworms (Acrobasis vaccinii Riley) are native to North America and have been classified as pests since the introduction of cranberry as an agricultural product (Tomlinson 1960). As larvae, these moths are the primary pest of large fruit cranberries and a significant pest of highbush blueberries (Fitzpatrick 2008).